2009
DOI: 10.1590/s1415-790x2009000200015
|View full text |Cite
|
Sign up to set email alerts
|

Tendência da mortalidade por homicídios no Estado do Paraná, segundo Regionais de Saúde, 1979 a 2005

Abstract: A tendência da mortalidade por homicídios de homens de 15 a 49 anos residentes no Paraná foi analisada no período de 1979 a 2005. Foram calculados coeficientes de mortalidade por homicídio (por 10(5) homens de 15 a 49 anos) por Regionais de Saúde (RS) de residência, agrupados em triênios e analisados por meio de média móvel e da variação percentual anual (VA%) de acordo com os seguintes estratos: muito baixo: < 40; baixo: de 41 a 55; médio: de 56 a 70; alto: de 71 a 85; e muito alto: > 86. De 1979-1981 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
2
0
3
Order By: Relevance
“…However, the present study points to a downward trend in mortality rates in border regions and an increase in deaths in non-border regions and the state as a whole over the study period. These findings are consistent with studies showing that state the has the highest homicide rates in the country's South region 1,10 . A nationwide study of violence showed different realities in states that have seen a decrease in homicide rates: Espírito Santo (-27.6%), Paraná (-23.4%), and Alagoas (-21.8%) 1 .…”
Section: Discussionsupporting
confidence: 92%
“…However, the present study points to a downward trend in mortality rates in border regions and an increase in deaths in non-border regions and the state as a whole over the study period. These findings are consistent with studies showing that state the has the highest homicide rates in the country's South region 1,10 . A nationwide study of violence showed different realities in states that have seen a decrease in homicide rates: Espírito Santo (-27.6%), Paraná (-23.4%), and Alagoas (-21.8%) 1 .…”
Section: Discussionsupporting
confidence: 92%
“…differences in living conditions represent a significant determinant in the socio-spatial distribution of violent deaths 13,14,20,34,35,36,37 . Likewise, international investigations conducted in other socio-cultural contexts, even using different methodologies and theoretical approaches, indicate that local disadvantaged groups have a higher risk of violence, suggesting an association between inequality and homicide 38,39,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Estados das regiões Nordeste e Norte foram os que mais contribuíram para o aumento do homicídio em municípios de diferentes portes populacionais. Taxas de homicídio de grande magnitude nos estados destas regiões coincidem com intensa e desordenada urbanização em suas capitais, marcadas por crescimento econômico e desigualdades 15,25,[33][34][35][36] . Fatores socioeconômicos são relacionados à violência em diferentes localidades do país.…”
Section: Métodosunclassified
“…A mudança de padrão de mortalidade por homicídio observada neste estudo indica certa recomposição da violência no espaço nacional, caracterizada por ampliação e certo grau de interiorização desses eventos 14,23,[33][34][35][36] . A expansão e a integração de zonas urbanas aproximam variados tipos de cidades e aglomerados regionais e permitem algum efeito de contágio, o que pode fazer parte da explicação do fenômeno de interiorização da violência identificado nesse estudo [36][37][38] .…”
Section: Métodosunclassified